The trees : a novel - Everett, Percival; OverDrive, Inc. (Minneapolis, Minnesota : Graywolf Press, 2021)
After a series of brutal murders in a rural Mississippi town, investigators arrive and discover a large number of similar cases that all have roots in the past.
When a pair of detectives from the Mississippi Bureau of Investigation arrive to investigate a series of brutal murders in the rural town of Money, they meet expected resistance from the local sheriff, his deputy, the coroner, and a string of racist White townsfolk. The murders present a puzzle, for at each crime scene there is a second dead body: that of a man who resembles Emmett Till. The detectives suspect that these are killings of retribution, but discover that eerily similar murders are taking place all over the country. As the bodies pile up, the MBI detectives uncover a history that refuses to be buried. -- adapted from back cover
Electronic book.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Murder -- Investigation -- Fiction; Racism -- Fiction; Murderers -- Fiction; Murder -- Investigation; Murderers; Racism; Mississippi -- Fiction; Mississippi; Detective and mystery fiction; Fiction; Novels; Fiction; Novels; Detective and mystery fiction; Electronic books; Thriller fiction; Detective fiction; Mystery fiction